2008
DOI: 10.1111/j.1551-2916.2008.02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CuO on the Sintering Temperature and Piezoelectric Properties of (Na0.5K0.5)NbO3 Lead‐Free Piezoelectric Ceramics

Abstract: When a small amount of CuO was added to (Na 0.5 K 0.5 )NbO 3 (NKN) ceramics sintered at 9601C for 2 h, a dense microstructure with increased grains was developed, probably due to liquidphase sintering. The Curie temperature slightly increased when CuO exceeded 1.5 mol%. The Cu 21 ion was considered to have replaced the Nb 51 ion and acted as a hardener, which increased the E c and Q m values of the NKN ceramics. High piezoelectric properties of k p 5 0.37, Q m 5 844, and e 3 T /e 0 5 229 were obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…The increased T T À O of LKNNTAS-CuO piezoceramics indicates that the orthorhombic phase is dominant at room temperature, in consistent with the analysis of XRD patterns. The dielectric properties of LKNNTAS piezoceramics decrease with the addition of CuO, showing similar tendency to the previous work [15][16][17]. P r are 12.6 μC/cm 2 and 13.0 μC/cm 2 , respectively.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The increased T T À O of LKNNTAS-CuO piezoceramics indicates that the orthorhombic phase is dominant at room temperature, in consistent with the analysis of XRD patterns. The dielectric properties of LKNNTAS piezoceramics decrease with the addition of CuO, showing similar tendency to the previous work [15][16][17]. P r are 12.6 μC/cm 2 and 13.0 μC/cm 2 , respectively.…”
Section: Methodssupporting
confidence: 87%
“…On the other hand, CuO has been proved as an effective sintering aid for many kinds of piezoceramics. But it is also reported that the addition of a large amount of CuO will induce undesirable secondary phases, which deteriorates piezoelectric properties [15][16][17]. According to the above considerations, proper …”
Section: Introductionmentioning
confidence: 92%
“…4.5. However, the T c did not C for 10 h [15] increase further as the CuO addition increased, indicating that only a small amount of Cu ion was incorporated into the NKNC matrix. Since the radius of the Cu 2+ ion (0.73 Å ) is similar to that of the Nb 5+ ion (0.64 Å ), the Cu 2+ ion is thought to replace the Nb 5+ ions and transform the NKNCs into hard ceramics.…”
Section: Low Temperature Sintering Mechanism and Piezoelectric Propermentioning
confidence: 83%
“…4.4 [15]. However, when the CuO content exceeded 1.0 mol%, peaks for the CuO second phase indicated by the arrows, were observed.…”
Section: Low Temperature Sintering Mechanism and Piezoelectric Propermentioning
confidence: 84%
“…CuO is often used because of its low melting point and formation of liquid phase. Park et al [75] elaborately studied the effect of CuO on KNN ceramics. They observed that addition of CuO decreases the sintering temperature of KNN below 1000°C in order to prevent the Na 2 O evaporation and to eventually improve the piezoelectric properties by increasing their polling efficiency.…”
Section: Knbo 3 -Based Ceramicsmentioning
confidence: 99%